Sufism: Spiritual and Cultural Traditions in India - Mratkhuzina, Guzel Ferdinandovna; Bobkov, Dmitriy Vyacheslavovich; Khabibullina, Alfiya Marselevna; Ahmad, Ishtiak Gilkar (Journal of History Culture and Art Research, 2019)
The relevance of the topic is determined by the necessity of further research of cultural and spiritual traditions in India, for the study of the history of Islam spread and establishment, and for development of the Sufi doctrine formation theory. Taking into account the local history aspect of the topic, we note that now we are seeing a gradual restoration of Sufism in Tatarstan. It is a reference to the past of Sufism in the region, an appeal to the religious heritage of the Tatar people. The leading approach to the study of this topic is the theoretical and conceptual, historical and scholarly understanding of continuity in the sequential study of this topic. This article aims to achieve the following aims: the analysis and evaluation of Sufism as a constituent of Indian culture, aimed at ensuring the implementation of modern ethical and aesthetic concepts of Sunni Islam, their transformation in the mass consciousness of the Muslim peoples of India. The main results of this study are the identification and development of the accumulated material on the stated topic, and further development of its theoretical and practical bases. Referring to centuries of experience and traditions of Islam, it is important to turn to the study of the history and philosophy of Sufism in the Indian subcontinent.